2018
DOI: 10.1039/c8cp03543a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of compatible solute ectoine on distinct DNA structures: thermodynamic insights into molecular binding mechanisms and destabilization effects

Abstract: We study ectoine-induced destabilization effects on DNA hairpins by a combination of atomistic molecular dynamics simulations, experiments, and theoretical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 88 publications
7
28
0
Order By: Relevance
“…5 Ectoine has a zwitterionic structure in the solid state 6 and in aqueous solution 7,8 at neutral pH. Its water structuring (kosmotropic) effects, 5,[7][8][9] role as a hydroxyl radical scavenger, 10,11 and influence on protein functions, 9,[12][13][14][15][16] gene expression, 17,18 DNA melting temperature, 12,19 DNA structure, 20,21 DNA-protein binding, 9,12 and protection of biomolecules against ionising radiation 10 and oxidative stress 22 were investigated over the last decade. Due to its versatile properties, ectoine is currently used in a multitude of biotechnological, cosmetic and medical applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Ectoine has a zwitterionic structure in the solid state 6 and in aqueous solution 7,8 at neutral pH. Its water structuring (kosmotropic) effects, 5,[7][8][9] role as a hydroxyl radical scavenger, 10,11 and influence on protein functions, 9,[12][13][14][15][16] gene expression, 17,18 DNA melting temperature, 12,19 DNA structure, 20,21 DNA-protein binding, 9,12 and protection of biomolecules against ionising radiation 10 and oxidative stress 22 were investigated over the last decade. Due to its versatile properties, ectoine is currently used in a multitude of biotechnological, cosmetic and medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only indirect information is available here. 9,20,21 Meyer et al observed structural changes in plasmid DNA after incubation with ectoine, without clarifying whether these effects were based on direct or indirect interactions between both molecules. 20 Computational work by Oprzeska-Zingrebe et al estimated that ectoine accumulates between 0.5-2 nm distance to the sugar-phosphate backbone of dsDNA due to electrostatic and dispersion interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Although the molecular details of the underlying mechanism are still not fully understood, most of the explanations attribute the resulting protein stabilization mechanism to a preferential exclusion of cosolutes around the macro-molecular compounds. [42][43][44][45][46][47][48] In the numerical simulation of ref. 45, a strong binding to DNA of ectoine was found, and was attributed to the highly negative charge of the DNA phosphodiester backbone via strong electrostatic interactions in combination with pronounced dispersion energies.…”
Section: The Condensing Force Of Dna By Magnetic Tweezers (Mt)mentioning
confidence: 99%
“…[42][43][44][45][46][47][48] In the numerical simulation of ref. 45, a strong binding to DNA of ectoine was found, and was attributed to the highly negative charge of the DNA phosphodiester backbone via strong electrostatic interactions in combination with pronounced dispersion energies. However, this binding is not so effective in the present case since the counterions in at least millimolar concentration exist in solution and they neutralize the most charge of the phosphodiester backbone.…”
Section: The Condensing Force Of Dna By Magnetic Tweezers (Mt)mentioning
confidence: 99%